Mitral valve surgery: comparison between superior septal and left atrial approaches: Surgical Approaches to the Mitral Valve - Taha, Abdulsalam Yaseen; Haji Saed, Shkar Raouf; Mohammed, Amanj Kamal; Nadr, Jivara Hama (Journal of the Faculty of Medicine Baghdad, 2021)
Background Mitral valve (MV) is one of the most complex structures in human heart with a challenging exposure. Traditionally, MV is approached via left atriotomy (LAA) while superior septal approach (SSA) is an alternative. Objective: is to highlight the merits and demerits of these two approaches in providing access to the MV in term of the aortic cross clamp time (ACCT), quality of exposure, and potential complications in view of the published literature. Patients and Method: Over an 18-month period ending at June 30th, 2019, 56 patients with MV disease ± other cardiac diseases were enrolled in this study. Twenty patients had surgery via LAA (one surgeon) whereas 36 were operated upon via SSA (another surgeon). Standard surgery was done via median sternotomy, cardiopulmonary bypass and hypothermia of 32 0C. Perioperative events were recorded. Results In SSA group (males=25; age ranged 23-74 years; mean=57.4), patients had chest pain and breathlessness for a mean of 3 months (>LAA) besides low ejection fraction (EF) in 44%, atrial fibrillation (AF) in 38.9% and dilated LA in 19.4%. They underwent 25 MV replacements (MVR), 11 MV repairs (0 in LAA), 11 coronary artery bypass grafts (CABGs) (2.6 graft per patient vs. 1.3 in LAA; significant) and 2 aortic valve replacement. Mean ACCT was 81.6 minutes (˂LAA). Postoperatively, 32 patients (88.9%) had a normal or improved EF, 11 of 14 AF patients (78.6%) reverted to sinus rhythm and no hospital death was recorded. Conclusion Besides excellent exposure, the SSA enabled us to perform MVR or repair ± additional interventions within a short time and without a heart block. Hence, our results matched the international literature.